ELECTROMAGNETIC SHIELDING AS A WAY OF PROTECTING INFORMATION FROM ITS LEAKAGE BY TECHNICAL CHANNELS - PAVLENKO, YEVHEN; STEPANOV, MIKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In this paper, investigated one of the way of protecting information from its leakages through the technical channels, such as shielding. The first part of the work mainly consider the theoretical principles of shielding, such as definition and process of shielding, its types, main task of the shield, highlighted the concept of shielding efficiency, presented dependence for calculating the efficiency of electromagnetic shield, provided shields classification according to three characteristics: type of field interference, design and material, shield forms, for each of them presented dependence for calculating shielding efficiency of magnetic and electromagnetic field, presented dependence for calculating depth of penetration, as a value that characterizes shielding effect of shielding material.The second part of work consider separate types of shielding such as shielding of the electric field, dependence for calculating its effectiveness, presented main requirements for electric shields, considered the principles of shielding for low-frequency and high-frequency magnetic fields, dependences for calculating its shielding efficiency,  presented main requirements for magnetostatic shields, considered shielding of electromagnetic fields, provided main mechanisms of protection against electromagnetic interference, presented dependence for calculating shielding efficiency of electromagnetic field.In the third part of the work calculated shielding efficiency and penetration depth of electromagnetic field for magnetic and non-magnetic materials at given frequencies with different conductivity and different thickness of shield walls, provided graphs of frequency dependence of shielding efficiency at different thickness of the shield walls, shown graph of frequency dependence of penetration depth for different materials, made conclusions and provided recommendations regarding selection of shielding materials at high and low frequencies, presented shielding materials for permanent magnetic field and  high-frequency electromagnetic field.
Keywords: technical protection of information; shielding; electromagnetic field; shielding effectiveness; shielding materials